Moroccan youth and the challenges of integration and public policies National Youth Strategy 2015-2030 as an example - Amachnoug, Rachid (Social Empowerment Journal, 2019)
The aim of this paper is to study the situation of Moroccan youth within the current public policies, especially in the National Youth Strategy 2015-2030 which was approved by the government in 2014. It is considered an important stage, it is constructed as a crucial moment between two approaches in the management of the issue of youth in Morocco. First, the sectoral vertical management -which was prevailing since the independence of Morocco- to which the various sectors of government and official institutions have been exposed without declared coordination or integrated work. Second, the Integrated horizontal strategic management, which seeks to form a common and shared vision and an integrated community project on youth issues and their expectations. However, there are some major disadvantages to be noted about the latter goal, the salient of which are the absence of the political will and sufficient commitment to implement the strategy and provide the appropriate conditions for its success. This means that the crisis of the Moroccan youth is not linked to programs, plans and strategies, but to the appropriate democratic political context for their implementation and evaluation of their effectiveness and impact.